Fluid restriction adherence and interdialytic weight gain associated with intradialytic mean arterial pressure among hemodialysis patients - Astri Zeini Wahida; Rima Novianti Utami (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Intradialytic mean arterial pressure (MAP) status is one of the most common cardiovascular indicators among patients with chronic kidney disease undergoing maintenance hemodialysis. Poor adherence to fluid restriction and excessive interdialytic weight gain (IDWG) are considered major contributors to hemodynamic alterations during dialysis sessions. Purpose: To examine the factors associated with intradialytic mean arterial pressure (MAP) among patients receiving maintenance hemodialysis. Method: An analytical cross-sectional study was conducted among patients with chronic kidney disease undergoing maintenance hemodialysis at a hospital in Indonesia. A total of 136 participants were recruited through a total sampling approach. Adherence to fluid restriction was measured using the Fluid Control in Hemodialysis Patients Scale (FCHPS), a 28-item instrument rated on a 5-point Likert scale, which demonstrated high internal consistency (Cronbach’s α = 0.88). Interdialytic weight gain (IDWG) was calculated as the percentage increase in body weight relative to the preceding post-dialysis dry weight. Intradialytic blood pressure was assessed using the mean arterial pressure (MAP) recorded two hours after initiation of dialysis. Data analysis was performed using multiple linear regression to examine associations between adherence and clinical outcomes. Results: Descriptive analysis showed a mean IDWG of 3.67% of dry body weight, a mean fluid restriction adherence score of 42.70, and a mean intradialytic MAP of 102.44 mmHg. Multiple linear regression demonstrated that interdialytic weight gain was positively associated with intradialytic MAP (β = 0.282, p = 0.001), whereas adherence to fluid restriction was negatively associated (β = −0.245, p = 0.003). Together, these variables explained 15.1% of the variance in intradialytic MAP (F = 13.000, p < 0.001). Conclusion: Adherence to fluid restriction and interdialytic weight gain are important variables associated with mean arterial pressure stability in patients undergoing maintenance hemodialysis. Continuous nursing education and behavioral interventions aimed at improving fluid management are essential to reduce the risk of acute cardiovascular complications in this patient population.